When endometriosis returns: managing vault involvement after hysterectomy: a case report - Sinha, Anuvi; Rahane, Tushar L.; Ghorpade, Niteen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Vault endometriosis is a rare but quite challenging condition occurring in post-hysterectomy patients. Minimally invasive surgery remains the gold standard for the diagnosis and management of such cases. We hereby present a case report of a 41-year-old lady who had undergone total laparoscopic hysterectomy 12 years ago and came with irregular vaginal bleeding since 7 to 8 years. She was thoroughly evaluated for the same and underwent biopsy of the growth over the vault, which was suggestive of endometriosis. Magnetic resonance imaging (MRI) was done to rule out involvement of the bladder and rectum. She underwent elective laparoscopic excision of an endometriotic nodule over the vault and bladder serosal shaving. Postoperatively patient was relieved of her signs and symptoms.